Impacts of neoliberal conservation on protected area governance: a case study of Hluhluwe-Imfolozi Park - O’Donoghue, Thomas Luke (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.